THE EFFECT OF EMPLOYEE ENGAGEMENT, CREDITOR ENGAGEMENT, GOVERNMENT ENGAGEMENT AND CUSTOMERS ENGAGEMENT ON QUALITY OF SUSTAINABILITY REPORTING IN INDONESIA - Suheri, Aisyah W (Indonesian Journal of Accounting and Governance, 2024)
This study aims to examine the effect of employee engagement, creditor engagement, government engagement and customer engagement on the quality of sustainability reports in energy, raw goods and non cylical companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The population in this study were energy, raw goods companies and non cylical listed on the Indonesia Stock Exchange for the 2019-2022 period. The sampling technique in this study used purposive sampling technique and obtained a sample of 39 companies. The data analysis method used is logistic regression analysis. The results of this study indicate that government engagement affects the quality of sustainability reports, while employee engagement, creditor engagement and customer engagement have no effect on the disclosure of sustainability reports.